A Description of Predatory Publishing in South African Economics Departments. (22nd January 2021) - Kerr, Andrew; de Jager, Phillip
Abstract: Predatory publishers charge fees to authors for open access publishing but have limited peer review or other quality controls. In this paper, we use data from five of the most widely used predatory journals used by South African academics in Economic and Management sciences to show that predatory publications are widespread in Economics departments in South African universities. We also critique the Department of Higher Education and Training's research publication subsidy system and highlight that several journals on the DHET accredited journal list, that South African academic economists publish in, are probable predatory journals. In improving the data on predatory publications in South African Economic and Management Sciences used by de Jager et al (2017), we show that approximately 50% of predatory publications by South African academic economists are authored by professors or associate professors, a finding which corroborates international evidence on predatory publications in Economics. Our paper is also a source of information on the quality of research produced by South African economics departments.